Predictions for the Isolated Diphoton Production through NNLO in QCD and Comparison to the 8 TeV ATLAS Data - Bouzid Boussaha; Farida Iddir; Lahouari Semlala (Advances in High Energy Physics)
We present cross-section predictions for the isolated diphoton production in next-to-next-to-leading order (NNLO) QCD using the computational framework MATRIX. Both the integrated and the differential fiducial cross-sections are calculated. We found that the arbitrary setup of the isolation procedure introduces uncertainties with a size comparable to the estimation of the theoretical uncertainties obtained with the customary variation of the factorization and renormalization scales. This fact is taken into account in the final result.